1982
DOI: 10.1159/000123298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chloroquine on Thyroliberin Interaction with Clonal Rat Prolactin Cells

Abstract: The lysosomotropic agent, chloroquine, has been used to investigate the implication of lysosomal activity and membrane traffic in TRH binding, TRH internalization and TRH-induced stimulation of prolactin secretion in a rat prolactin cell line (GH3/B6). Chloroquine by itself does not affect cell number, cell protein and basal prolactin secretion. It does not alter TRH binding and internalization as well as both effects of TRH on the stimulation of prolactin secretion, i.e., prolactin release and prolactin produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…To our surprise, the membrane of the GERL cisternae, which is particularly apparent in both PRL cell types, was never labeled with the A-Ly-M, whereas it always contained abundant acid phosphatase-positive material (22). There is a large overlap between the present results and previous staining with Golgi antibodies of the same cell types (25), since both antibodies label the membranes of medial saccules, lysosomes, and endosome-like vacuoles, but not the secretory granule membrane.…”
Section: Figure 3 Lmmunochemical Staining Of the Plasma Membrane Of Gmentioning
confidence: 70%
“…To our surprise, the membrane of the GERL cisternae, which is particularly apparent in both PRL cell types, was never labeled with the A-Ly-M, whereas it always contained abundant acid phosphatase-positive material (22). There is a large overlap between the present results and previous staining with Golgi antibodies of the same cell types (25), since both antibodies label the membranes of medial saccules, lysosomes, and endosome-like vacuoles, but not the secretory granule membrane.…”
Section: Figure 3 Lmmunochemical Staining Of the Plasma Membrane Of Gmentioning
confidence: 70%
“…To evaluate this hypothesis we applied compounds that disrupt ion channel processing and insertion at different stages in the protein synthesis-exocytosis pathway. Chloroquine (CQ) interferes with vesicle recycling [20], membrane fusion events [21], and Na + channel trafficking [10],[22],[23]. N-ethylmaleimide (NEM) is widely used to disrupt vesicle docking and recycling.…”
Section: Resultsmentioning
confidence: 99%
“…If CQ could inhibit endocytosis, metabolism of 3H Con A would be prevented. However, several investigators (21)(22)(23) have shown that CQ does not inhibit endocytosis to any appreciable degree.…”
Section: Discussionmentioning
confidence: 99%